Hołd pruski w pamięci Krakowa: Materiały z sesji naukowej odbytej 25 maja 2025 roku - Noga, Zdzisław (2026)
On April 10, 1525, a memorable ceremony known as the Prussian Homage took place in Kraków. It marked the culmination of lengthy negotiations between Poland and the Teutonic Order, which had concluded with the signing of the Treaty of Kraków two days earlier. It ended a long-standing conflict and simultaneously opened a new chapter in relations between the Kingdom of Poland and Prussia, ruled by Albrecht Hohenzollern, the last Grand Master and henceforth its first secular ruler, who was required to pay homage to the Polish King Sigismund the Old in Kraków’s Main Square.This day of Polish glory was used to lift spirits during difficult times of national enslavement for Poles. It was immortalized in paintings, including Jan Matejko’s most famous work, displayed in the Hall of the “Prussian Homage” in the Cloth Hall. Other artists, such as Tadeusz Kantor, also referenced this event. Also of interest are the celebrations of the anniversaries of this event at Wawel in the 19th and 20th centuries, which can be traced through the lens of the press of the time. Finally, the memory of this event takes a different form among Poles than among Germans.The authors of the texts included in the book did not engage in a discussion of the consequences of the Treaty of Kraków and the Prussian Homage, focusing instead on the memory of this event, which gained a second life, so to speak, in the works of artists who popularized it and made it one of the most famous events from the distant past.
Keywords: hołd pruski; Zygmunt Stary; Albrecht Hohenzollern; Kraków; rok 1525